2019
DOI: 10.1002/cam4.2553
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of circular RNAs, transforming growth factor‐β, and long noncoding RNAs in hepatocellular carcinoma

Abstract: At the heart of hepatocellular carcinoma (HCC) lies disruption of signaling pathways at the level of molecules, genes, and cells. Non‐coding RNAs (ncRNAs) have been implicated in the disease progression of HCC. For instance, dysregulated expression of circular RNAs (circRNAs) has been observed in patients with HCC. As such, these RNAs are potential therapeutic targets and diagnostic markers for HCC. Long non‐coding RNAs (lncRNAs), a type of ncRNA, have also been recognized to participate in the initiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 167 publications
(365 reference statements)
1
12
0
1
Order By: Relevance
“…As a crucial downstream component of the Wnt signaling pathway, mutations and increased nuclear expression of β-catenin have been detected in human HCC specimens [30]. And TGF-β modulates various microenvironment factors involved in HCC through intrinsic or extrinsic signaling pathway [31]. In this study, we clarify a significant correlation between expression of CBX8 and EMT associated markers in HCC cells and tissues, supporting a role of CBX8 playing in HCC progression and metastasis.…”
Section: Discussionsupporting
confidence: 61%
“…As a crucial downstream component of the Wnt signaling pathway, mutations and increased nuclear expression of β-catenin have been detected in human HCC specimens [30]. And TGF-β modulates various microenvironment factors involved in HCC through intrinsic or extrinsic signaling pathway [31]. In this study, we clarify a significant correlation between expression of CBX8 and EMT associated markers in HCC cells and tissues, supporting a role of CBX8 playing in HCC progression and metastasis.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, high-throughput genome and transcriptome sequencing and microarrays have indicated that apart from protein-coding genes, 75% of the human genomeis transcribed into noncoding RNAs [ 8 ]. LncRNAs are functionally catalogued as noncoding transcripts, are more than 200 nucleotides in length, and have no protein-coding potential.…”
Section: Introductionmentioning
confidence: 99%
“…16 The actions of lncRNAs are mediated by diverse molecular mechanisms, such as transcriptional modulation, chromatin remodeling, histone modification, regulation of mRNA splicing, and the competing endogenous RNA (ceRNA) mechanism. 17,18 Existing studies have identified a close relation between lncRNAs and human cancers. [19][20][21] Much evidence suggests that numerous lncRNAs are differentially expressed in melanoma, and their dysregulation is involved in melanoma progression because lncRNAs can act as oncogenic factors or tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%